Search for the optimal size of printed circuit boards for mechanical structures for electronic equipment - Yefimenko, A. A.; Karlangach, A. P.; Lazarev, S. N. (Technology and design in electronic equipment, 2014)
The authors present a method, an algorithm and a program, designed to determine the optimal size of printed circuit boards (PCB) of mechanical structures and different kinds of electronic equipment. The PCB filling factor is taken as an optimization criterion. The method allows one to quickly determine the dependence of the filling factor on the size of the PCB for various components.